2015
DOI: 10.1530/erc-15-0386
|View full text |Cite
|
Sign up to set email alerts
|

CYP19A1 fine-mapping and Mendelian randomization: estradiol is causal for endometrial cancer

Abstract: Candidate gene studies have reported CYP19A1 variants to be associated with endometrial cancer and with estradiol (E2) concentrations. We analyzed 2937 single nucleotide polymorphisms (SNPs) in 6608 endometrial cancer cases and 37 925 controls and report the first genome wide-significant association between endometrial cancer and a CYP19A1 SNP (rs727479 in intron 2, P=4.8×10−11). SNP rs727479 was also among those most strongly associated with circulating E2 concentrations in 2767 post-menopausal controls (P=7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
79
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 46 publications
(62 reference statements)
5
79
0
Order By: Relevance
“…Finally, there are similarities in tumor phenotype and/or shared tissue of origin between endometrial cancer, the benign gynaecological condition endometriosis, the endometrioid and clear cell histologies of ovarian cancer, and basal-like breast cancer(2527). Thus, pooling ovarian and endometrial(23, 28, 29) cases could uncover novel loci.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, there are similarities in tumor phenotype and/or shared tissue of origin between endometrial cancer, the benign gynaecological condition endometriosis, the endometrioid and clear cell histologies of ovarian cancer, and basal-like breast cancer(2527). Thus, pooling ovarian and endometrial(23, 28, 29) cases could uncover novel loci.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, meta-analysis of data for 7,737 endometrial cancer cases and 37,144 controls of European ancestry from three GWAS datasets (ANECS, SEARCH, and NSECG) and two followup datasets (iCOGs and NSECG Phase 2) identified rs2498796 (OR ¼ 1.12 for the minor A allele, 95% CI:1.07-1.17, p value ¼ 3.55 3 10 À8 ) as the top SNP representing a single association signal at the 14q32.33 endometrial cancer risk locus. 6 For the current study we employed an in silico fine-mapping approach 12 previously used to fine-map other endometrial cancer risk loci, 4,5,13,14 focussing on the 1Mb region surrounding rs2498796 (bases 104,743,220-105,743,220; NCBI build 37/hg19 assembly). The current analysis utilized genotyped and imputed SNP data for the three GWAS (ANECS, SEARCH, and NSECG) and the iCOGs follow-up datasets and included a total of 6,608 endometrial cancer cases and 37,925 controls (details of these datasets can be found in 4,5 ).…”
Section: Methodsmentioning
confidence: 99%
“…6 For the current study we employed an in silico fine-mapping approach 12 previously used to fine-map other endometrial cancer risk loci, 4,5,13,14 focussing on the 1Mb region surrounding rs2498796 (bases 104,743,220-105,743,220; NCBI build 37/hg19 assembly). The current analysis utilized genotyped and imputed SNP data for the three GWAS (ANECS, SEARCH, and NSECG) and the iCOGs follow-up datasets and included a total of 6,608 endometrial cancer cases and 37,925 controls (details of these datasets can be found in 4,5 ). The Cheng et al analysis had included a total of 420 genotyped and imputed SNPs with minor allele frequencies (MAF) R1% and information scores R0.9 per dataset within the focal region.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CYP19A1 gene is located on the chromosome 15 at 15q21.2 and it mainly encodes CYPs aromatase, which involves converting testosterone to estradiol and androstenedione to estrone respectively [5,6]. Most studies of the CYP19A1 gene are about hormone-related cancers, such as the breast cancer, prostate cancer, and endometrial cancer, and some research of them found that they are directly related to endogenous and exogenous steroid hormones that affect cell proliferation [7][8][9][10]. These results suggest that CYP19A1 gene may be associated with the development of tumors.…”
Section: Introductionmentioning
confidence: 99%